Effect of the government policies towards abandoned housing project in Malaysia - Nur Asyikin, Ruhannudin (2017)
The issue of abandoned building happens across the globe, and it brings nothing positive to the stakeholders as well as to the country economy. In Malaysia, this issue has grown to an unbearable state, and this study aims to study the abandoned building in Malaysia. Abandoned was the project including the building, civil engineering and heavy engineering development project for example houses, schools, bridges, roads, high rise building and others that been abandoned. The issue of abandoned projects is still an unsettled issue in Malaysia. Even though there are numerous policies and laws have been promulgated by the Malaysian government, yet the problem of abandoned housing projects is still occurring and has not yet been fully addressed. In this study, the questionnaire survey and review on literature will be conducted to evaluate effect of government policies towards abandoned housing project around Malaysia and the cause of abandonment. The expected outcomes of this study are to provide methods of prevention for the issue and reviving solutions to the abandoned building in Malaysia. A minimum 50 questionnaires survey were distributed randomly to contractor, consultant, developer, government, and others. The questionnaires forms were distributed through the social network, e-mail and also by hand using questionnaire form. The 42 sets of questionnaire were used and as the analyzed in this research. Relative Index Inequality (RII) is adopted to evaluate the ranking of different factors by the respondents. From the results, it shows that the cause of government policies towards abandoned housing project is the lack of enforcement of housing law and policy as one of the main contributing factors of abandoned housing projects and the house buyers are not adequately protected under the existing law and practices. The precautionary steps should take before start the project to avoid the abandoned housing project happen, where the legality of the developer should be tracked.